Mastering soft skills in the implementation of work-based learning among community college students - Ali, A.; Mahmod, S. (PERTANIKA Universiti Putra Malaysia Press, 2017)
Various efforts have been taken by the Ministry of Education (MOE) and the Ministry of Higher Education Malaysia (MOHE) to improve the country’s education system. Learning methods were introduced to ensure the education system achieves the desired educational goals and produces individuals who are well-balanced spiritually, emotionally and physically. However, the issue of graduate unemployment often crops up in the mass media; more often than not, the discussion has centred on the failure of tertiary educational institutions to churn out quality graduates. Thus, the method of work-based learning (WBL) is seen as a way to improve the soft skills of local graduates. This study was conducted using the quantitative research survey, with an adapted questionnaire as the instrument. Data were analysed using the Statistical Package for the Social Science (SPSS) version 20. The respondents consisted of 97 students who attended WBL programmes at five community college i.e. Community College Selayang, Community College Ampang, Community College Kota Melaka, Community College Sg. Petani and Community College Besut. The findings revealed that the level of soft skills among community college students was high. The soft skills included communication skills, problem-solving skills, learning and information management skills, profession related ethnics skills and leadership skills. This study of community college studentsis significant because it identified the level of soft skills of students who had performed WBL methods. The findings of this study can help community colleges to produce high-quality graduates, hence reducing the number of unemployed graduates.